SMAD4 enhances the cytotoxic efficacy of human NK cells against colorectal cancer cells via the m6A reader YTHDF2 - Li, Xinxin; Wang, Yilin; Cai, Lei; Huang, Siyong (Frontiers in Immunology, 2024)
Colorectal cancer (CRC) ranks as the third most prevalent malignant neoplasm in terms of both morbidity and mortality. Within the tumor microenvironment (TME) of CRC, the diminished presence and diminished cytotoxic function of natural killer (NK) cells serve as primary factors driving the advancement of CRC; however, the precise regulatory mechanisms governing this phenomenon remain incompletely understood.Consequently, the identification of novel, potential anti-CRC targets associated with NK cells emerges as a pressing and paramount concern warranting immediate attention.We examined the regulatory mechanism of SMAD4-mediated NK cell cytotoxicity on CRC by utilizing samples from CRC patients, mouse models of CRC, and various experimental techniques. Our findings revealed that the expression of SMAD4 is decreased in NK cells within the TME of human CRC. Furthermore, we observed that enforced upregulation of SMAD4 resulted in enhanced cytotoxicity of NK cells towards CRC cells. Furthermore, our research has revealed that YTHDF2 functions as a downstream effector of SMAD4, playing a crucial role in the control of transcription and translation of m 6 A-modified RNA. Moreover, our investigation demonstrated that increased expression of SMAD4 promoted the activated receptor NKG2D by elevating levels of YTHDF2. Ultimately, the SMAD4-YTHDF2 regulatory axis-significantly enhanced the cytotoxicity of NK cells against human CRC cells. Our study unveils a novel mechanism through which SMAD4 modulates the cytotoxicity of NK cells towards CRC cells, suggesting that SMAD4 may hold promise as a potential therapeutic target for NK cell therapy in CRC.